2003
DOI: 10.1177/00343552030460020201
|View full text |Cite
|
Sign up to set email alerts
|

Training Needs of Certified Rehabilitation Counselors for Contemporary Practice

Abstract: In order to meet the demands of today's rehabilitation counseling practice environments effectively, rehabilitation counselors must be well prepared in traditional, as well as emerging, knowledge areas. The purpose of this study was to determine the training needs of certified rehabilitation counselors practicing in a variety of settings by identifying knowledge areas perceived by counselors as important for which they also reported limited preparation levels. Results of the analysis revealed 23 knowledge area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
42
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 4 publications
(6 reference statements)
1
42
0
Order By: Relevance
“…Another way to analyze this data is to examine knowledge scores by a technique shown by Chan et al (2003), which divided answers into categories of excellent knowledge and preparation for scores of 4 and 5 and needs improvement for scores of 1 or 2. In this study, when preparation scores were examined in this manner, it was found that CRCs report a need for improvement on all 25 preparation items assessed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another way to analyze this data is to examine knowledge scores by a technique shown by Chan et al (2003), which divided answers into categories of excellent knowledge and preparation for scores of 4 and 5 and needs improvement for scores of 1 or 2. In this study, when preparation scores were examined in this manner, it was found that CRCs report a need for improvement on all 25 preparation items assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have been conducted in the past to attempt to identify the areas of knowledge and skill that rehabilitation counselors perceive they are deficient in as a result of education and training programs lacking adequate coverage of said areas in course curricula and which they believe are essential to their professional roles. Chan et al (2003) surveyed certified rehabilitation counselors (CRCs) in the field to evaluate the training needs of rehabilitation counselors based on their perceptions of preparation compared to knowledge needed in the field. Similarly, Froehlich and Linkowski (2002) assessed the training needs of state VR counselors to find areas of high discrepancy between the importance of training in specific areas and preparedness.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Clients with substance abuse issues continue to fuel referrals for services (U.S. Department of Health and Human Services retrieved 6-2-11 from http://oas.samhsa.gov/ NSDUH/2k9NSDUH/2k9Results.htm#1.4). Rehabilitation service providers have acknowledged the importance of substance abuse treatment although they may lack the preparedness to deal with the problems (Chan et al, 2003). Research has found that graduate students continue to feel inadequately trained to provide substance abuse services (Madson, Bethea, Daniel, & Necaise, 2006), and rehabilitation professionals also feel inadequately trained although 85% of their clients have substance abuse issues (Ong, Cardoso, Chan, Chronister, & Chou, 2007).…”
mentioning
confidence: 99%
“…rehabilitation professionals are not receiving adequate training in these practice domains (Cardoso et al, 2006;Cardoso, Romero, Chan, Dutta, & Rahimi, 2007;Chan et al, 2003;Emener, Evans, Lowe, & Richard, 2001;Ingraham, Kaplan, & Chan, 1992;Lee, Chronister, Tsang, Ingraham, & Oulvey, 2005;Ong et al, 2007). Previous studies have addressed the need to provide training in substance abuse treatment and assessment among rehabilitation professionals to better serve clients in rehabilitation settings Machlan, Brostand, & Benshoff, 2005;Ong et al, 2007).…”
mentioning
confidence: 99%